Mitigation of NaCl by effect of a biostimulant in the germination of Ocimum basilicum L. - Batista Sánchez, Daulemys; Murillo Amador, Bernardo; Nieto Garibay, Alejandra; Alcaráz Meléndez, Lilia; Troyo Diéguez, Enrique; Hernández Montiel, Luis Guillermo; Ojeda Silvera, Carlos Michel (REVISTA TERRA LATINOAMERICANA, 2017)
Biostimulants activate the process of seed germination and act in physiological functions. They contain substances of plant metabolism, which allow better use of nutrients and they can mitigate stress caused by salinity. The objective of this study was to evaluate the effect of a natural biostimulant (FitoMas-E®) to mitigate salinity in the stage of germination of the basil varieties (Ocimum basilicum L.) Emily, Napoletano and Nufar. The seeds were subjected to concentrations of NaCl (0, 50, 100 and 150 mM) and doses of FitoMas-E® (0, 0.5, 1 and 1.5 mL L-1) under controlled conditions. The experimental design was completely randomized with factorial arrangement and four replications. The variables evaluated were germination percentage and rate, seedling height, radicle length, fresh and dry radicle biomass, fresh and dry shoot biomass. The results showed that seedling height, radicle length, fresh shoot biomass and dry radicle biomass in 150 mM were the most damaged. Napoletano and Nufar showed greater radicle length in 0 mM. As NaCl concentration increased, radicle length decreased signif icantly in the three varieties. Seedlings from seeds treated with FitoMas-E® increased radicle length; Napoletano in 1 mL L-1 and Nufar in 0.5 mL L-1 were the varieties that showed higher values. Napoletano showed greater fresh shoot biomass in 0 mM with 0.5 mL L-1 of FitoMas-E®. Napoletano seedlings from seeds treated with 0.5 mL L-1 of FitoMas-E® increased dry radicle biomass in 0 and 50 mM of NaCl. It is concluded that FitoMas-E® at doses of 0.5 and 1 mL L-1 mitigates the effect of moderate to severe saline stress on basil seeds.